Behavior of Outrigger Wall and Wall Belt Supported System under Lateral Loads in a Structure: A Review - Das, Urjal; Pal, Ankit; Vishwakarma, Arvind (International Journal of Advanced Engineering Research and Science, 2020)
Every Structure needs a table to withstand a system of resisting other forces caused by wind or strong earthquakes. One of the best programs is outrigger. Outriggers of structural elements support the formation of lateral loads together. When the complexity of the height of the buildings is increased they become larger as well as the addition of tempting additions to resist systems such as truss consists of belt and outriggers is needed. Utilization of structural regulation adds structural strength by connecting the main building with the remote colony and making the whole body function as a single unit in resistance to the burden. The current review articles deals with the research based on the Outrigger Wall and Wall Belt Supported System by different researchers. The observation includes based on the reviews in that inputs of Outrigger Wall and Wall Belt increase the performance of building in terms of stability, stiffness, strength & cost. It also concluded that this performance are vary with variation is occurs in the location and dimensions parameters such height, depth and plan areas. The research also impact on the system is used as per the guidelines provided.